The role of internal marketing in improving service quality: A study of service companies - Rachman Mulyandi; B Wishman S` Siregar; Elizabeth Elizabeth; Ridnawati Ridnawati; Dede M. Riski (Privietlab, 2026)
This study examines the role of internal marketing in improving service quality at service companies. The research method employed in this study is a qualitative approach using a literature review. This study highlights that internal marketing significantly increases employee satisfaction, engagement, and commitment, which ultimately has a positive impact on the quality of service provided. Effective internal marketing practices, such as good communication, training, and recognition, play a crucial role in boosting employee motivation and performance. The research findings confirm that internal marketing is a strategic investment in human resource management that can optimize organizational performance by improving service quality. By prioritizing internal marketing, companies can create a work environment conducive to innovation, collaboration, and employee well-being, thereby supporting the achievement of sustainable organizational performance.